Azerbaijan and Israel: Oil, Islam and Strawberries Pragmatism in Foreign Policy Between Unlikely Allies - Marcus, Robert (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: My thesis analyzes the unique bilateral relationship developed between the nations of Azerbaijan and Israel. Extensive cooperation has occurred in the areas of energy movement, politics, trade, and the fight against radical Islam. This relationship is a true demonstration of pragmatism in foreign policy between unlikely allies, which has important strategic implications for the United States of America.